2023
DOI: 10.1177/02698811231154111
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine rechallenge or continuation despite neutropenia or agranulocytosis using colony-stimulating factor: A systematic review

Abstract: Objectives: Rechallenge/continuation of clozapine in association with colony-stimulating factors (CSFs) following neutropenia/agranulocytosis has been reported, but many questions remain unanswered about efficacy and safety. This systematic review aims to assess the efficacy and safety of rechallenging/continuing clozapine in patients following neutropenia/agranulocytosis using CSFs. Methods: MEDLINE, Embase, PsycInfo, and Web of Science databases were searched from inception date to July 31, 2022. Articles sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
(80 reference statements)
0
0
0
Order By: Relevance
“…Results showed that agranulocytosis severity had no significant impact on the treatment outcome. However, the efficacy and safety of this strategy remain unclear [229].…”
Section: Haematological Side Effectsmentioning
confidence: 99%
“…Results showed that agranulocytosis severity had no significant impact on the treatment outcome. However, the efficacy and safety of this strategy remain unclear [229].…”
Section: Haematological Side Effectsmentioning
confidence: 99%